2005
DOI: 10.1128/aem.71.12.8183-8190.2005
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the nifH Gene of a Herbaspirillum Endophyte in Wild Rice Species: Daily Rhythm during the Light-Dark Cycle

Abstract: The expression of nitrogenase genes of Herbaspirillum sp. B501 associated in shoot (leaf and stem) of wild rice, Oryza officinalis, was studied by means of reverse transcription-PCR (RT-PCR) targeted at the nifH gene. RT-PCR analyses indicate that nifH transcript was detected exclusively from nitrogen-fixing cells of gfp-tagged strain B501gfp1 in both free-living and endophytic states by using a constitutive gfp gene transcript as a positive control. Transcription of nifH and nitrogen fixation in free-living c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 34 publications
0
39
0
Order By: Relevance
“…A few years ago, it has been reported that root exudates from several plant secrete compounds that mimic AHLs (Teplitski et al, 2000;Gao et al, 2003;Mathesius et al, 2003) as these can activate bacterial AHL biosensors; however, their chemical structure and precise biological source are currently unknown. It appears that densities of endophytic bacteria, if rice colonization-infection experiments are performed, are usually low, lower than 10 7 cells g À1 (James et al, 2002;You et al, 2005). In addition through the use of the specific AHL AiiA-lactonase, it was observed that these compounds are very sensitive to the enzyme and therefore are most likely AHLs or have a very related lactone structure.…”
Section: Discussionmentioning
confidence: 99%
“…A few years ago, it has been reported that root exudates from several plant secrete compounds that mimic AHLs (Teplitski et al, 2000;Gao et al, 2003;Mathesius et al, 2003) as these can activate bacterial AHL biosensors; however, their chemical structure and precise biological source are currently unknown. It appears that densities of endophytic bacteria, if rice colonization-infection experiments are performed, are usually low, lower than 10 7 cells g À1 (James et al, 2002;You et al, 2005). In addition through the use of the specific AHL AiiA-lactonase, it was observed that these compounds are very sensitive to the enzyme and therefore are most likely AHLs or have a very related lactone structure.…”
Section: Discussionmentioning
confidence: 99%
“…In experiments similar to the present ones, only one alternative nitrogenase gene was found to be preferentially expressed in spite of the existence of remarkably diverse nifH sequences in the termite gut microbial community 23) . Many environmental factors such as the O2 concentration and nitrogen sources 12,42) might limit or regulate nifH gene expression in plants.…”
Section: Resultsmentioning
confidence: 99%
“…Beacon Designer software (Premier Biosoft International, Palo Alto, CA) was used to design the nosZ primer set (nosZ2F, 5Ј-GTCGTC ATCTTCAACCTCAAG; nosZ2R, 5Ј-TATTCATGCCATGCGGATTG). Total RNA was prepared as described previously (53). Quantitative reverse transcription-PCR analysis was carried out by the i-Cycler optical system (Bio-Rad Laboratories, Inc., Tokyo, Japan) as described previously (53).…”
mentioning
confidence: 99%
“…Total RNA was prepared as described previously (53). Quantitative reverse transcription-PCR analysis was carried out by the i-Cycler optical system (Bio-Rad Laboratories, Inc., Tokyo, Japan) as described previously (53).…”
mentioning
confidence: 99%